Knowledge and perception of Ghanaian cocoa farmers on mirid control and their willingness to use forecasting systems. (3rd February 2016) - Awudzi, Godfred Kweku; Asamoah, Mercy; Owusu-Ansah, Frank; Hadley, Paul; Hatcher, Paul Edwin; Daymond, Andrew James
Abstract : Annual losses of cocoa in Ghana from mirids are significant; therefore, accurate timing of insecticide application is critical to enhance yields. However, cocoa farmers often lack information on the expected mirid population for each season to enable them to optimize pesticide use. This study assessed farmers' knowledge and perceptions of mirid control and their willingness to use forecasting systems informing them of the expected mirid peaks and the time of pesticide application. A total of 280 farmers were interviewed in the Eastern and Ashanti regions of Ghana with a structured open- and closed-ended questionnaire. Most farmers (87%) considered mirids the most important insect pest on cocoa, with 47% of them attributing 30–40% of annual crop losses to mirid damage. There was a wide variation in the timing of insecticide application as a result of farmers using different sources of information to guide the start of application. The majority of farmers (56%) did not have access to information about the type, frequency and timing of insecticide use. However, respondents who were members of farmer groups had better access to such information. Extension officers were the preferred channel for information transfer to farmers, with 72% of farmers preferring them to other available methods of communication. Almost all the respondents (99%) saw the need for a comprehensive forecasting system to help farmers manage cocoa mirids. The importance of the accurate timing of mirid control based on forecasted information to farmer groups and extension officers is discussed.